2007
DOI: 10.1104/pp.107.098558
|View full text |Cite
|
Sign up to set email alerts
|

barren inflorescence2Encodes a Co-Ortholog of thePINOIDSerine/Threonine Kinase and Is Required for Organogenesis during Inflorescence and Vegetative Development in Maize

Abstract: Missouri 63121 (S.M., E.K.)Organogenesis in plants is controlled by meristems. Axillary meristems, which give rise to branches and flowers, play a critical role in plant architecture and reproduction. Maize (Zea mays) and rice (Oryza sativa) have additional types of axillary meristems in the inflorescence compared to Arabidopsis (Arabidopsis thaliana) and thus provide an excellent model system to study axillary meristem initiation. Previously, we characterized the barren inflorescence2 (bif2) mutant in maize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(174 citation statements)
references
References 71 publications
(114 reference statements)
4
170
0
Order By: Relevance
“…Recently, one of the rice PIN1-like genes has been implicated in tiller bud outgrowth and adventitious root initiation (31), but its contributions to inflorescence structure are not known. Furthermore, the maize BIF2 (co-ortholog of PINOID-like serine/threonine kinase) regulates the initiation of axillary meristem and lateral primordia (32), underscoring the importance of auxin signaling for primordia emergence in grasses. Our data provide starting points for further investigations on RFL mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one of the rice PIN1-like genes has been implicated in tiller bud outgrowth and adventitious root initiation (31), but its contributions to inflorescence structure are not known. Furthermore, the maize BIF2 (co-ortholog of PINOID-like serine/threonine kinase) regulates the initiation of axillary meristem and lateral primordia (32), underscoring the importance of auxin signaling for primordia emergence in grasses. Our data provide starting points for further investigations on RFL mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants in rice and maize (Zea mays) coorthologs for Arabidopsis auxin biosynthesis factors, auxin transport, and signaling factors display defects in inflorescence axillary meristem development, spikelet and FM initiation, and organ numbers and organ development (McSteen et al, 2007;Morita and Kyozuka, 2007;McSteen, 2010;Phillips et al, 2011). Our microarray data showed that the second largest functional category of affected genes encodes signaling factors, and we note global effects on auxin metabolism and response (Supplemental Table S3; Supplemental Fig.…”
Section: Osmads1 Regulates Oskanadi2 and Oskanadi4 Expressionmentioning
confidence: 99%
“…Moreover, ZmPIN1a activity rescues Arabidopsis pin1-3, resulting in the re-establishment of auxin maxima and the re-formation of FMs, which indicates that the auxin transport mechanism during FM initiation might be conserved between Arabidopsis and grasses (Gallavotti et al, 2008b). Interestingly, the phosphorylation and localization of ZmPIN1a is also regulated by a homologue of PID, BARREN INFLORESCENCE2 (BIF2) (McSteen et al, 2007;Skirpan et al, 2009), which suggests similarities in the regulation of auxin transporter trafficking between maize and Arabidopsis. In rice (Oryza sativa), OsPID, another orthologue of PID, has been suggested to function in polar auxin transport (Morita and Kyozuka, 2007), but its role in FM initiation is so far unknown.…”
mentioning
confidence: 93%